The Role of Human Endogenous Retroviruses in the Initiation and Progression of Melanoma - Yao Lin; Rosanna Rita Satta; Elena Rita Simula; Shijie Tang; Paola Molicotti; Antonio Cossu; Corrado Rubino; Leonardo Antonio Sechi (Biomedicines)
Human endogenous retroviruses (HERVs), as remnants of ancient exogenous retroviruses in the human genome, have received increased attention regarding their pathogenic effects caused by abnormal activation. In normal somatic cells, HERVs are tightly regulated by epigenetic mechanisms and are rarely expressed. In cancer cells, likely due to epigenetic dysregulation, HERVs become abnormally activated and are transcribed and expressed. The innate and adaptive immune responses triggered by HERV activation are closely associated with cancer initiation and progression. Melanoma, as a malignant tumor, often exhibits a poor prognosis in advanced-stage patients. HERVs have been found to be expressed in melanoma and linked to its malignant transformation. Here, we review the potential roles HERVs may play in melanoma development. As promising therapeutic targets for melanoma, research on HERVs could facilitate the development of novel treatment strategies.